Effects of neutral polysaccharide from Platycodon grandiflorum on high-fat diet-induced obesity via the regulation of gut microbiota and metabolites - Song, Jing; liu, Qin; Hao, Mengqi; Zhai, Xiaohu; Chen, Juan (Frontiers in Endocrinology, 2023)
The obesity epidemic has become a global problem with far-reaching health and economic impact. Despite the numerous therapeutic efficacies of Platycodon grandiflorum, its role in modulating obesity-related metabolic disorders has not been clarified. In this study, a purified neutral polysaccharide, PGNP, was obtained from Platycodon grandiflorum. Based on methylation and NMR analyses, PGNP was found to be composed of 2,1-β-D-Fruf residues ending with a (1→2)-bonded α-D-Glcp. The protective effects of PGNP on high-fat HFD-induced obesity were assessed. According to our results, PGNP effectively alleviated the signs of metabolic syndrome, as demonstrated by reductions in body weight, hepatic steatosis, lipid profile, inflammatory response, and insulin resistance in obese mice. Under PGNP treatment, intestinal histomorphology and the tight junction protein, ZO-1, were well maintained. To elucidate the underlying mechanism, 16S rRNA gene sequencing and LC-MS were employed to assess the positive influence of PGNP on the gut microbiota and metabolites. PGNP effectively increased species diversity of microbes and reversed the HFD-induced imbalance in the gut microbiota by decreasing the Firmicutes to Bacteroidetes ratio. The abundance of Bacteroides and Blautia were increased after PGNP treatment, while the relative abundance of Rikenella, Helicobacter were reduced. Furthermore, PGNP notably influenced the levels of microbial metabolites, including the increased levels of cholic and gamma-linolenic acid. Overall, PGNP might be a potential supplement for the regulation of gut microbiota and metabolites, further affecting obesity.